South African Television Moves into the Global Age - Teer-Tomaselli, Ruth (The Routledge Companion to Global Television, 2019)
Television delivery throughout the world has changed rapidly over the past two decades. Within South Africa, much of this global narrative is repeated. The last 25 years saw a move from a single monopoly broadcaster within the ‘public service’ tradition (but later subsumed into the apartheid political agenda), to the present situation of a multi-company, multi-platform, increasingly digital delivery, calling into question even the very definition of ‘broadcasting’. ‘Global difference’ in South Africa plays out through a relatively late start but surprisingly short catch-up period, emphasizing a demographic/socio-economic specificity that has resulted in a highly skewed television market in which the uptake of high-end technology is less widespread than in other more ‘developed’ markets, and where the taste of local programming dominates even the technologically advanced sectors. The move toward a digital system, together with the introduction of competition, has provided challenges to the regulatory regime. The majority of the audience share, however, remains with local programming, regardless of its delivery.
Num Pages: 11
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Auteur.rice; Afrique du Sud (corpus analysé); Afrique du Sud (lieu de production du savoir); _Nettoyé